Weaving Emotions and Culture: The Success Story of Teh Botol Sosro’s Packaging on Indonesia’s 75th Independence Day West Java and DKI Jakarta Edition - Setiawan, Andri; supriatna, Supriatna; Wartika, Enok (PANTUN: Jurnal Ilmiah Seni Budaya, 2023)
Teh Botol Sosro, the first ready-to-drink tea beverage in Indonesia, introduced a new packaging theme of “Independence and the Cultural Diversity of Indonesia” to celebrate Indonesia’s 75th Independence Day. The research aims to analyze the significant role of the concepts and themes of independence and Indonesia’s cultural diversity in building a solid emotional connection with consumers. The research methodology used qualitative analysis focusing on visual communication, gathering data through visual analysis and expert interviews. The research findings reveal that utilizing these elements, analyzed through Marc Gobe’s emotional branding concept, successfully establishes a solid emotional connection with consumers. This is reflected in a deeper understanding of national values and cultural diversity, as well as the introduction of a profound emotional dimension in the consumer experience. In conclusion, this research highlights the vital role of these concepts and themes in creating a significant emotional bond with consumers and enhancing the product’s appeal.